Peran Serikat Pekerja Dan Karyawan Dalam Mewujudkan Good Corporate Governance - Nugroho, Arif (Universitas Serang Raya, 2014)
Implementation of Good Corporate Governance (GCG) driven by two objectives:the implementation of Good Corporate Citizenship and the interests strengthening of the company and economy.Attention employee relationship with companies that implement good corporate governance with two objectives:1. Employee have the benefit of the company is growing. Employee need income for survival and self- actualization of the company. Because it requires continuity of income for their livelihoods, they also need employee who have continuity of work where continuity of their business. 2. Employee have an interest in the fulfillment of the rights of employee. Labor as a factor of production need to be treated well and secure their rights in accordance with the Act in force, so that the industrial relations that occur going well. Employee and Labor Union in GCG implementation can act as a responsible wishetlblower, which is intended only for the betterment of the company, not for personal interest or a certain group or competitor companies. Besides as wishetlblower also play an active role in the creation and implementation of the Perjanjian Kerja Bersama (PKB) with respect to internal and external conditions, so there is always harmony between the employer / company management in order to progress